1989
DOI: 10.2170/jjphysiol.39.825
|View full text |Cite
|
Sign up to set email alerts
|

Complicated central effects of endothelin on blood pressure in rats.

Abstract: The role of endothelin (ENT) in the control of systemic blood pressure (BP) was examined in conscious rats. Intracerebroventricular (i.c.v.) administration of ENT (0.002 or 0.2 jig, i.e., 0.78 or 78 pmol/2 µl 0.9% saline) to conscious rats had complicated effects on BP. A significant fall in BP occurred in the initial 2-4 min after administration; and then after recovery toward the control level, BP decreased again within 17 min, following which a constant rise in BP occurred. In addition to the changes in BP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Circulating endothelin was also found to influence the area postrema neurons. Minamisawa et al [1989], on the other hand, found a decrease followed by an increase of BP after ICV administration of ET in conscious rats. ET administered in the cisterna magna produced an immediate rise in the BP, renal nerve activity, and HR [Kuwaki et al, 1990a,b].…”
Section: Cardiovascular Systemmentioning
confidence: 89%
“…Circulating endothelin was also found to influence the area postrema neurons. Minamisawa et al [1989], on the other hand, found a decrease followed by an increase of BP after ICV administration of ET in conscious rats. ET administered in the cisterna magna produced an immediate rise in the BP, renal nerve activity, and HR [Kuwaki et al, 1990a,b].…”
Section: Cardiovascular Systemmentioning
confidence: 89%
“…Increased activity of the sympathetic nervous system has long been recognized to play a role in SHR hypertension (8). Some reports have also suggested that AVP mediates the pressor response to ET-1 (17,18,21). However, ET-1 prompts equivalent increases in the Long Evans rat and its mutant counterpart, the Brattleboro rat, which lacks circulating AVP (27).…”
Section: E21mentioning
confidence: 99%
“…ET-1 injections into the lateral cerebral ventricle consistently increase systemic arterial pressure in rats, but the heart rate response varies (17,21,27,28,31). In contrast, intracisternal injection or application of ET-1 to the ventral medulla evokes a biphasic response, with an initial increase followed by a decrease in arterial pressure (6,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation